“Hidden” sequence periodicities and protein architecture - Rackovsky, S. (The National Academy of Sciences, 1998)
I demonstrate the existence in protein domain sequences of sets of statistically significant periodic signals, characteristic of the architectures of those domains. It is shown that, although the frequencies of the signals characteristic of a particular architecture have definite wave numbers, they can occur in any physical property. The characteristic signals define sequence units, which may correspond to specific structural features. Study of signals in different architectures suggests that symmetric structures are characterized by sets of sequence signals, which are members of harmonic series and which therefore impose commensurate periodicities on the structure. Asymmetric structures are characterized by mutually incommensurate sets of sequence signals. It is pointed out that, although these periodic sequence units can be very short, their existence is a property of the entire sequence.